A inserção internacional dos governos locais : o caso da Secretaria Municipal de Relações Internacionais de Belo Horizonte (MG) - Lima, Daiane Pedro de (2015)
This paper has the purpose of to discuss the characteristics of municipal institutional arrangement of international relations and the impact of its work on public policies carried out by municipal institutions of city hall. For that, initially, the determining factors that legitimate the international action of the sub-national governments were found, subsequent to, we done an observation of the characteristics of municipal institutions of international relations of Brazil. Finally, we analyzed the institutionalization of international action of a particular subnational government as well as the activities that have been done by institution that takes care of external works, and we analyzed the governmental management of this organism. We examined too how is its involvement with other municipal institutions. Aiming at exemplify this matter, a case study of the International Relations Municipal Sub-Secretariat of Belo Horizonte/MG was done, because the Law 9.011/2005, which institutionalized this organism, recommends that this organism should work together with the other municipal institutions so that it can fulfill the purposes described in this same law.